2022
DOI: 10.3389/fcvm.2022.911393
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary survival and anticoagulation of patients with atrial fibrillation: A community based cohort study in China

Abstract: BackgroundsThe understanding of death in patients with atrial fibrillation (AF) in China is limited. This study aimed to assess the contemporary survival of AF patients in China and to explore risk factors for deaths.MethodsThis was a prospective community-based cohort study including 559 AF patients, who were followed-up from July 2015 to December 2020.ResultsDuring 66-month follow-up, there were 200 deaths (56.5% cardiovascular, 40.0% non-cardiovascular, and 3.5% unknown causes) among 559 AF patients with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In patients with HF with reduced ejection fraction, the prevalence of AF ranges from 36.7% to 44.9%, and in those with HF with preserved ejection fraction, the AF prevalence is between 40% and 50% [14]. Importantly, HF is a major cause of mortality in AF patients, as evidenced by a Chinese community study showing that HF is the leading cause of death in persistent AF patients [15]. A meta-analysis suggests that catheter ablation can improve the prognosis and quality of life of patients with AF combined with HF [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with HF with reduced ejection fraction, the prevalence of AF ranges from 36.7% to 44.9%, and in those with HF with preserved ejection fraction, the AF prevalence is between 40% and 50% [14]. Importantly, HF is a major cause of mortality in AF patients, as evidenced by a Chinese community study showing that HF is the leading cause of death in persistent AF patients [15]. A meta-analysis suggests that catheter ablation can improve the prognosis and quality of life of patients with AF combined with HF [4].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, HF is a major cause of mortality in AF patients, as evidenced by a Chinese community study showing that HF is the leading cause of death in persistent AF patients [15]. A meta-analysis suggests that catheter ablation can improve the prognosis and quality of life of patients with AF combined with HF [4].…”
Section: Value Of Lsp-af Catheter Ablationmentioning
confidence: 99%
“…Previous works have reported that approximately 15% to 31% of paroxysmal AF patients at the early-stage progress to persistent or permanent AF during a time period between 4 and 8 years ( 17 ). Although AF itself poses little threat to life, ischemic stroke caused by AF is one of the main causes of death (17%) in Chinese community patients with AF ( 15 ). To optimize the early management of AF patients and slow down the progression of AF, Chinese guideline ( 16 ) provides suggestions for AF risk prediction by age and this has been demonstrated by many studies that there is a positive association between the incidence of AF and advancing age ( 18 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension was defined as systolic blood pressure (SBP) ≥ 140 mmHg, diastolic blood pressure (DBP) ≥ 90 mmHg, or current antihypertensive therapy. Diabetes mellitus was defined as a previous diagnosis of diabetes mellitus, treatment with oral hypoglycemic agents or insulin, or having a fasting plasma glucose ≥ 126 mg/dL (7.0 mmol/L) or hemoglobin A1c level ≥ 6.5% ( 15 ). Heart disease is defined as a previous diagnosis of heart failure or coronary heart disease.…”
Section: Methodsmentioning
confidence: 99%